(untitled) (Revista Brasileira Multidisciplinar, 2009)
The State of Sao Paulo, as well as several other Brazilian states, has suffered an intense process of devastation of its natural heritage, resulting in the loss of about 80% of its native vegetation, with consequences for its fauna. The main objective of the research was to survey data and information on relevant scientific studies, completed or not, involving the issue of biodiversity in the region of UGRHI – Tietê-Jacaré (SP). Therefore, consultations were held in the databases of the Biota-Fapesp, in the Ministry of Environment, in the Environmental Secretary of Sao Paulo and in municipal sites. Among the results, we can point out the mapping of research institutions and their work done on biodiversity in the region, besides quantitative data on the remaining natural vegetation and an inventory of protected areas and other specially protected areas existing in the UGRHI. The integration of data and information contained in this work can serve as subsidies to the creation and implementation of public policies for conservation and preservation of biodiversity, which may, in turn, stimulate the relationship between local governments, the Watershed Committee Tietê-Jacaré and academic institutions.